Glomus Tumors of 20 Cases’ Experience - Muhammed Uslu; Nilsen Yıldırım Erdoğan; Ozan Beytemür (Bagcilar Medical Bulletin, 2025)
Objective: This study aimed to analyze the clinical characteristics, surgical outcomes, and long-term follow-up of glomus tumors in a single-center experience. Method: A retrospective analysis was conducted on 20 patients who underwent surgery for histologically confirmed glomus tumors between 2013 and 2023. Patient demographics, tumor characteristics, clinical presentation, radiological findings, surgical outcomes, and follow-up data were collected and analyzed. Results: The cohort consisted of 75% females, with a mean age of 45.5±17.3 years. Most tumors (85%) were located in the hand, with 65% in the subungual region. The most common symptoms were tenderness (100%), visible tumor (85%), cold sensitivity (80%), and pain (70%). Radiological findings were positive in 70% of cases. The median tumor size was 0.6 cm, with significantly larger tumors in males compared to females (p=0.0245). The median preoperative duration was two years, and the median follow-up was 3.5 years. A 5% recurrence rate was observed post-surgery. Conclusion: This study provides valuable insights into the clinical presentation and surgical management of glomus tumors. The findings highlight the effectiveness of surgical excision, with a low recurrence rate. The correlation between positive radiological findings and longer preoperative duration suggests potential diagnostic delays, emphasizing the need for increased awareness and prompt intervention in suspected cases.